Fifth Five Year Plan (1974-79) Proposals For Annual Plan 1975—76 (Volume II) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1974)
The tropical climate of this Territory is responsible for rapid multiplication of different pests and diseases. The cultivated areas are mostly surrounded by forests which provide alternative hosts. Thus pests and diseases are present in active form throughout the year. Heavy and continuous rains £ are received for 7 to 3 months a year which restricts the number of working days.
Andaman and Nicobar Administration
Andaman and Nicobar Administration